ANALISIS PEMBELAJARAN IPA BERBASIS PERMAINAN TEKA-TEKI DALAM MENINGKATKAN MINAT BELAJAR SISWA DI SEKOLAH DASAR SEBUAH TINJAUAN LITERATUR - Liza Adelia Putri; Widya Pratiwi Nawawi; Dian Ayu Nurani; Abila Desti Amanda (Mimbar PGSD Flobamorata, 2023)
This research aims to investigate the effect of using puzzle games in science learning on students’ interest in learning at the elementary school level. A literature review reveals that a learning approach that involves puzzle game elements can increase students’ interest in learning. Several important findings in the literature include that the use of puzzle games in learning can make the science learning process more interesting and enjoyable for students. Puzzle games can stimulate students’ critical thinking and problem-solving skills, which are important skills in science learning. This type of research is a library study or library research with a library data collection method carried out by reading and recording journals, articles, ebooks. The research results show that students who are involved in puzzle game-based learning tend to be more enthusiastic and participate actively in learning. Previous research also shows that the use of puzzle games can strengthen relationships between teachers and students and increase learning motivation. However, it is important to note that the effectiveness of this learning method can vary depending on its implementation and student characteristics. Further research is needed to measure the impact of using puzzle games in science learning in more depth, as well as to understand how contextual factors can influence students’ interest in learning. In elementary school.